Conceptualising Change on the WWW: Capturing the Constructivist Approach in Web-Based Learning among Engineering Lecturers - Guan, Eng Chan (2003)
The Information and Communication technology such as the WWW presents itself as a medium for channeling creative and collaborative learning. The extraordinary growth of the WWW necessitates engineering educators to look into their pedagogic approach to capture the ever-expanding knowledge and technological advancement in their area of expertise. This study attempts to look into the various factors related to the adoption of the WWW and the way the constructivist approach is related to the adoption of the WWW. The target population for this study are engineering lecturers from Polytechnics in Malaysia. Stratified sampling is applied to ensure that representative samples from the respective engineering departments are obtained in this study, namely the Civil Engineering, the Mechanical Engineering and the Electrical Engineering Department. The sampling size for this study was 500 engineering lecturers and the selection was based on the table of random numbers. The researcher visited all Polytechnics in Malaysia to conduct the questionnaire research except Sabah and Sarawak. The response rate for this study was 75.6%. The findings indicated that the four major factors namely organisational, technological, human, and training factors were significantly related with the adoption of the WWW. The human factor had the highest correlation coefficient value with the adoption model (r = 0.560, Q < 0.05) whereas the organisation factor had the lowest correlation value with the adoption model (r = 0.469, Q < 0.05) among the variables investigated. The other factors that had shown significant relationship with the adoption of the WWW were the technological factor (r = 0.541, Q < 0.05) and training factor (r = 0.511, Q < 0.05). Further multiple linear regression analysis showed that these four factors contributed about 50% of the explained variance of the adoption of the WWW.